Microwave Photonic Systems for Demodulation of Optical Fiber Interference Signals - Yuru Chen; Xiaohua Lei; Xianming Liu; Peng Zhang (Photonic Sensors, 2024)
Abstract Fiber optic sensors have been gradually used in aerospace, petrochemical, electronic power, civil engineering, and biomedical fields because of their many advantages such as the anti-electromagnetic interference, corrosion resistance, light weight, small size, high accuracy, and easy reuse. In recent years, sensing and demodulation technologies based on microwave photonics have attracted widespread attention. Optical fiber sensing combined with microwave photonics has higher sensitivity and flexibility, which is important for the demodulation of interferometric signals. This article introduces and analyzes the principle, structure, and performance of the demodulation technology of fiber optic interferometric signals based on microwave photonics from the perspective of system structures, such as filters, oscillators, and interferometers, and discusses the future research and development directions.